The Effect of Servqual, Social Media Marketing, and Facilities on Interest in Admission at Private Islamic University of Jember through Brand Religiosity Image as an Intervening Variable - Soraya Firdausi Nuzzila; Budi Santoso; Nursaid Nursaid (Universitas KH. Abdul Chalim Mojokerto, 2026)
The main objective of this study is to analyze the influence of service quality, social media marketing, and facilities on students' interest in registering with brand religiosity as an intervening variable. This study adopted a quantitative approach with a numerical method using the Partial Least Square (PLS) technique with WarpPLS 8.0 software. The population used in this study were active students of private universities in Jember Regency, with a total sample of 250 respondents, selected using non-probability sampling. Information was collected through a Likert scale survey and examined through validity and reliability checks, as well as structural model testing. The results showed that Servqual, Social Media Marketing, and Facilities influenced Interest in Registering and Brand Religiosity. Brand Religiosity has a positive and significant influence on Interest in Registering. However, Servqual, media marketing, and facilities have a positive and significant indirect effect on the Interest in registering through Brand Religiosity.